Cerebrosides from a Far‐Eastern Glass Sponge Aulosaccus sp. Issue 1 (11th December 2014) - Santalova, Еlena А.; Denisenko, Vladimir А.; Dmitrenok, Pavel S.; Drozdov, Аnatoly L.; Stonik, Valentin A.
Abstract: Nine new cerebrosides1a–d, 2a, 2b, 3a–c were found in the extract of a Far‐Eastern glass sponge Aulosaccus sp. (class Hexactinellida). These β ‐d ‐glucopyranosyl‐(1 → 1)‐ceramides contain sphingoid bases (2 S, 3 S, 4 R, 11 Z )‐2‐aminoeicos‐11‐ene‐1, 3, 4‐triol (in1a –d ), (2 S, 3 S, 4 R, 13 Z )‐2‐aminoeicos‐13‐ene‐1, 3, 4‐triol (in2a, b ) and (2 S, 3 S, 4 R, 13 S *, 14 R *)‐2‐amino‐13, 14‐methylene‐eicosane‐1, 3, 4‐triol (in3a –c ), which are N ‐acylated by (2 R, 15 Z )‐2‐hydroxydocos‐15‐enoic (in1a, 2a, 3a ), (2 R, 16 Z )‐2‐hydroxytricos‐16‐enoic (in1b, 2b, 3b ), (2 R, 17 Z )‐2‐hydroxytetracos‐17‐enoic (in1d ) and (2 R )‐2‐hydroxydocosanoic (in1c, 3c ) acids. The monoenoic and cyclopropane‐containing sphingoid bases of compounds1a–d, 2a, 2b, 3a–c have not been found previously in any sphingolipids. The structures of the cerebrosides were elucidated on the basis of 1 H‐, 13 C‐NMR spectroscopy, mass spectrometry, optical rotation data and chemical transformations. A simplified method for the assignment of the absolute configuration of 2‐hydroxy fatty acids by GC analysis of their (2 R )‐ and (2 S )‐oct‐2‐yl esters was proposed.